PSYCHOLOGICAL CONDITIONS FOR MAINTAINING READING SKILLS IN THE INFORMATION AGE - Soatov Asadulloh Djabborovich (The Conference Hub, 2025)
The article analyzes that reading books is a positive means that influences a person's mental processes (attention, intuition, perception, memory, imagination, thinking, speech), feelings (emotions, motivation, will), morality, behavior (play, study, work), worldview.
Keywords: book, skill, thinking, memory, attention, imagination, interest, knowledge, goal, result.